Studi Analisis Teori: Knowledge And Inovation Management Dalam Meningkatkan Sumber Daya Manusia Di Bidang Kesehatan - Cicik Khildar Rizqi; Vip Paramarta; Budi Setyorini; Candra Mizwar; Wo’i Megah Mayang Sari Paraisu (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2023)
Knowledge and innovation management is a knowledge management is a way of managing knowledge so that it can be distributed to organizations and can be studied by organizations in order to achieve the goals of the organization in terms of creating a product process that can affect organizational performance. Management of human resources (HR) is important in achieving the goals of an organization or agency. The purpose of this theoretical analysis is to find out how knowledge and innovation management improves human resources in the health sector. The research method used is a theoretical analysis study. Theoretical analysis as analysis in order to ensure that the theories used as analytical tools to dissect the problems in research are scientifically correct. The core of this theoretical analysis is knowledge and innovation management in the health sector, namely in terms of human factors, organization and strategy. It can be concluded that Knowledge management in innovation has become something that is very decisive, therefore its acquisition and utilization needs to be managed properly in the context of improving organizational or agency performance. In addition, strong management is also needed so that this knowledge takes root in every individual in the organization, always improving resource skills that can be supported by infrastructure for disseminating information within organizations and agencies. For institutions in the health sector, it is urgently needed how to apply to employees and health workers related to increasing skills through knowledge management and innovation. Employees or health workers must be able to acquire knowledge, make knowledge into institutional assets, apply the knowledge acquired and protect this knowledge as an asset that must be maintained and developed in providing health services to patients and also the importance of improving human resources.